2015
DOI: 10.1177/2158244015571186
|View full text |Cite
|
Sign up to set email alerts
|

Love in Connectedness

Abstract: Spirituality is important when caring for the whole human being. Earlier research found Love in connectedness to be a core category in spirituality. The study aim is to deepen our understanding of Love in connectedness, and contribute to the theoretical knowledge development of the concept of spirituality from a caring science perspective. The method was a review of 20 research articles concerning connectedness and love, which were interpreted through a Gadamerian-based hermeneutical approach. Emerging themes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…In the beginning, my intention was to study what it means to patients who are seriously ill when the spiritual dimension is integrated into a holistic practice. Spiritual care is well described in nursing literature, but there are multiple definitions (i.e., McSherry & Jamieson, 2011;Noble & Jones, 2010;Rykkje, Eriksson, & Raholm, 2013). Spiritual care often is described as caring activities related to patients' spiritual needs (Cook, Breckon, Jay, Renwick, & Walker, 2012;Milligan, 2011 as a social event and in the aesthetic indulgence of a well-set table or the arrangement of food in small, appetizing portions.…”
Section: Exploring Lived Experiencementioning
confidence: 98%
See 1 more Smart Citation
“…In the beginning, my intention was to study what it means to patients who are seriously ill when the spiritual dimension is integrated into a holistic practice. Spiritual care is well described in nursing literature, but there are multiple definitions (i.e., McSherry & Jamieson, 2011;Noble & Jones, 2010;Rykkje, Eriksson, & Raholm, 2013). Spiritual care often is described as caring activities related to patients' spiritual needs (Cook, Breckon, Jay, Renwick, & Walker, 2012;Milligan, 2011 as a social event and in the aesthetic indulgence of a well-set table or the arrangement of food in small, appetizing portions.…”
Section: Exploring Lived Experiencementioning
confidence: 98%
“…Discussing spiritual care can be difficult if we do not incorporate religious matters. In studying spiritual care, researchers tend to integrate specific questions about people's religious affiliations (i.e., Dobratz, 2013;McSherry & Jamieson, 2011;Rykkje et al, 2013), even if the research points at existential life meaning aspects. This enhances the idea that spiritual care is about religious matters.…”
Section: Exploring Lived Experiencementioning
confidence: 99%
“…Sub-study III (Rykkje et al 2015) searched for a deeper understanding of love and connectedness, through a theoretical literature review. This investigation found that connectedness is a concept of great significance inherent in human spirituality and which serves as a unifying force.…”
Section: A Theoretical Study Of Love In Connectednessmentioning
confidence: 99%
“…Although the separation and independence of human attributes are the basis for the creation of love, people have to communicate with each other to have a better life. 5 The nursing profession is the based on caring. Care is the combination of love and respect for others.…”
Section: Introductionmentioning
confidence: 99%
“…They have postulated that the flame of love in nursing is dimed and that some of nurses do not care for their clients with love. 5 Some have also reported that modern nursing has deviated from love because of the large workload, lack of time, low numbers of nurses, financial problems and short-term employment. Naturally, caring without love is a defective care, and this is a challenge for the nursing profession today.…”
Section: Introductionmentioning
confidence: 99%